In Silico Study of Eugenol and trans-Caryophyllene also Clove Oil Fumigant Toxicity on Tribolium castaneum: In Silico Study and Fumigant Toxicity of Clove Oil - Silvi Ikawati; Toto Himawan; Alvan Fajarudin; Abdul Latief Abadi; Hagus Tarno (Journal of Tropical Life Science, 2022)
Alternative storage pest control that is more environmentally friendly than the use of synthetic chemical pesticides is to use botanical pesticides from plant essential oils, including clove (Syzygium aromaticum) which contains the main compounds eugenol and trans-caryophyllene. To study the various mechanisms of action of essential oils as botanical insecticides could use in silico approach through molecular docking. This study aims to predict the dominant binding mode(s) of a ligand with a protein of a known three-dimensional structure through docking. Then tested its fumigant activity on Tribolium castaneum. The docking results showed that the trans-caryophyllene and eugenol compounds had a more stable bond strength in the acetylcholinesterase enzyme T. castaneum than the control compound linalool. In addition, there is a synergy between eugenol and trans-caryophyllene when the two compounds interact with acetylcholinesterase. These results can be used as prediction material that trans-caryophyllene and eugenol have potential as protein acetylcholinesterase inhibitors of T. castaneum. After being tested in the laboratory, clove oil which contains two main compounds namely eugenol and trans-caryophylene has the potential to control T. castaneum with an LC50 value of 5,227 ÃŽÂ¼L/L air. Keywords: Botanical insecticide, Caryophyllene, Docking, Eugenol, Fumigant,Syzygium aromaticum